Assessment of hydrological response to multiyear drought: Insights from lag characteristics and shift magnitude. Issue 7 (4th July 2022) - Li, Miao; Li, Shuzhen; Liu, Qiang; Kang, Yinhong; Liang, Liqiao; Yuan, Xiaomin; Zhang, Junlong; Wang, Xuan; Li, Chunhui
Abstract: The analysis of the hydrological response to meteorological drought events can lead to a deeper understanding of alterations in hydrological processes that can be used to help maintain environmental flow (e‐flow) in aquatic ecosystems. In this study, we first identified an extreme meteorological drought event and then assessed its hydrological response. Monthly precipitation anomalies were used to identify meteorological drought, while the Lyne–Hollick method (LH filter) was used alongside the baseflow recession constant (calculated using the Automatic Baseflow Identification Technique [ABIT]) to isolate baseflow in the Baiyangdian basin. Results showed that an extreme meteorological drought event occurred in August 1996, continuing for a total of 127 months, which resulted in prolonged hydrological drought (i.e., streamflow and baseflow). A time lag was generally observed between the end of the meteorological drought event and the end of the hydrological drought event, where baseflow recovery lagged behind streamflow (runoff) recovery. Additionally, drought led to an unstable shift in the precipitation‐streamflow relationship that subsequently led to a reduction in the annual streamflow of coinciding annual precipitation compared with the historical relationship. Drought also led to a longer response between precipitation and runoff events. Results from this study show that the hydrological response to meteorological drought event is important for water resource management and for addressing effects related to climate change, especially extreme drought events. Abstract : An extreme meteorological drought event occurred in August 1996, which resulted in prolonged and lagged hydrological drought (i.e., streamflow and baseflow), especially baseflow recovery lagged behind streamflow (runoff) recovery. Drought led to an unstable shift in the precipitation‐streamflow relationship that subsequently led to a reduction in the annual streamflow of coinciding annual precipitation compared with the historical relationship. Longer time lags between precipitation and runoff events in the precipitation‐streamflow relationship existed in drought.